On local Lipschitz regularity for quasilinear equations in the Heisenberg group. (November 2021) - Mukherjee, Shirsho
Abstract: The goal of this article is to establish local Lipschitz continuity of solutions for a class of sub-elliptic equations of divergence form, in the Heisenberg Group. The considered hypothesis for the growth and ellipticity condition is a natural generalization of the sub-elliptic p -Laplace equation and more general quasilinear equations with polynomial or exponential type growth.